Student Interest in Traditional Sports in the Era of Society 5.0 - Ahmad Al Munawar; Diego Gunawan Girsang; Dimas Sugiarto; Delima Lestari Sitorus; Devira Devira; Muhammad Ali Syahbana; Dipa Pangestu; S. Ahmad Habibi (Education Achievement: Journal of Science and Research, 2024)
Given the strong connection between physical activities, such as sports, and factors like quality of life, health, and overall well-being, it is crucial for every person to cultivate an interest in sports. Many sports that are popular throughout the community are categorised as "traditional." Traditional sports are activities that take place on a flat or level surface and involve the use of conventional equipment. There are two sorts of characteristics, namely intrinsic and extrinsic variables, that can impact an individual's inclination for traditional athletics. The investigation sought to ascertain the level of enthusiasm for conventional sports among students at Bina Guna STOK. This inquiry utilised quantitative descriptive analysis. The population being utilised refers to the group of students from the 2023 cohort at PJKR STOK Bina Guna Medan. The snowball sample technique, encompassing a total of fifty individuals, was employed. A questionnaire is a research tool that is utilised. The findings of the comprehensive analysis indicate that students at STIKP Pasundan have a significant inclination towards traditional sports, with a 4% share classified as "moderate," 58% as "high," and 28% as "very high." Based on the percentage of interest, the average value obtained for the interest of Bina Guna STOK students in traditional sports is classed as "High".